Problem-Based Learning Assisted by Physics Digital Pocket Book: Experimental Study to Enhance Students’ Critical Thinking Skills Completed with Bibliometric Analysis toward Sustainable Development Goals (SDGs) - Binar Kurnia Prahani; Shalsa Billa Ardhana Neswary; Hanandita Veda Saphira; Hidayah Binti Mohd Fadzil; Zavkiddin Mirtoshev; Jean Claude Uwayezu (ASEAN Journal of Educational Research and Technology, 2027)
This study presents a bibliometric and experimental investigation of Problem-Based Learning assisted by a Physics Digital Pocket Book (PhyPo) to enhance students’ critical thinking skills. Bibliometric analysis indicates increasing research interest in digital learning and problem-based approaches, while highlighting the limited integration of both in physics education. This study employed a true experimental design with a randomized pretest–posttest control group involving high school students. The results show that the implementation of PBL assisted by PhyPo was highly effective, leading to improved critical thinking skills and positive student responses. The integration of interactive digital media and inquiry-based learning enhances engagement and learning outcomes. These findings contribute to the advancement of innovative physics education aligned with sustainable development goals.